2020
DOI: 10.3390/jcm9020445
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mesenchymal Stromal Cells as Therapeutic Agents: Potential Mechanisms of Action and Implications in Their Clinical Use

Abstract: Due to the great therapeutic interest that involves the translation of mesenchymal stromal cells (MSCs) into clinical practice, they have been widely studied as innovative drugs, in order to treat multiple pathologies. MSC-based cell therapy involves the administration of MSCs either locally or systemically into the receptor body where they can traffic and migrate towards the affected tissue and participate in the process of healing. The therapeutic effects of MSCs compromise of different mechanisms such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 93 publications
(112 reference statements)
0
69
0
Order By: Relevance
“…However, it should be borne in mind that the direct effectors are still unclear, but it seems that the secretome of MSCs play an crucial role in suppression of tumors [64]. It should be stressed that various molecular mechanisms seem to be involved in therapeutic MSC actions in vivo and increase their regenerative potential [65]. Among others, direct MSC differentiation into cardiac and endothelial cells and the paracrine activity mediated by MSC-derived soluble molecules and vesicles are currently considered as major factors mediating beneficial effects of MSC-based therapies in various viable diseases [65][66][67][68][69].…”
Section: Mechanisms Of Msc-dependent Tumor Suppression In Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be borne in mind that the direct effectors are still unclear, but it seems that the secretome of MSCs play an crucial role in suppression of tumors [64]. It should be stressed that various molecular mechanisms seem to be involved in therapeutic MSC actions in vivo and increase their regenerative potential [65]. Among others, direct MSC differentiation into cardiac and endothelial cells and the paracrine activity mediated by MSC-derived soluble molecules and vesicles are currently considered as major factors mediating beneficial effects of MSC-based therapies in various viable diseases [65][66][67][68][69].…”
Section: Mechanisms Of Msc-dependent Tumor Suppression In Liver Cancermentioning
confidence: 99%
“…It should be stressed that various molecular mechanisms seem to be involved in therapeutic MSC actions in vivo and increase their regenerative potential [65]. Among others, direct MSC differentiation into cardiac and endothelial cells and the paracrine activity mediated by MSC-derived soluble molecules and vesicles are currently considered as major factors mediating beneficial effects of MSC-based therapies in various viable diseases [65][66][67][68][69]. However, recent studies showed that paracrine function of MSCs is the main mechanism by which these cells participate in tissue repair [68].…”
Section: Mechanisms Of Msc-dependent Tumor Suppression In Liver Cancermentioning
confidence: 99%
“…The use of MSCs in regenerative medicine has gained increasing popularity in recent years due to outstanding therapeutic potential of this cell type. They stimulate the organism's regenerative capacity in exerting a paracrine effect, producing cytokines and growth factors and thus pushing the on-site stem/progenitor cells and recruiting stem cells from other locations; besides, they are able to integrate into the damaged area [2].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, MSCs exert immunosuppressive effects by suppressing the secretion of proinflammatory factors while increasing the expression of anti-inflammatory mediators of immune cells [9,10], and on the other hand, MSCs regulate immune responses by eliciting the reprogramming of macrophages, suppressing the activation of B and T cells, and facilitating the proliferation of Treg cells [6,7,11,12]. Based on their immunomodulatory capacities, MSCs are prospective candidates for use in cellbased therapies for various immune and inflammatory diseases [13][14][15], but the application of these therapies is limited by difficulty in acquiring MSCs.…”
Section: Introductionmentioning
confidence: 99%